In situ estimation of tendon material properties: differences between muscles of the feline hindlimb - Cui, Lei (2009)
Recent experiments to characterize the short-range stiffness (SRS) – force relationship in several cat hindlimb muscles suggested that the there are differences in the tendon elastic moduli across muscles (Cui et al. 2007a). Those conclusions were inferred from whole muscle experiments and a computational model of SRS. The present study sought to directly measure tendon elasticity, the material property most relevant to SRS, during physiological loading to confirm the previous modeling results. Measurements were made from the medial gastrocnemius (MG), tibialis anterior (TA), and extensor digitorum longus (EDL) muscles during loading. For the latter, the model indicated a substantially different elastic modulus than for MG and TA. For each muscle, the stress-strain relationship of the external tendon was measured in situ during the loading phase of isometric contractions conducted at optimum length. Young’s moduli were assessed at equal strain levels (1%, 2% and 3%), as well as at peak strain. The stress-strain relationship was significantly different between EDL and MG/TA, but not between MG and TA. EDL had a more apparent toe region (i.e., lower Young’s modulus at 1% strain), followed by a more rapid increase in the slope of the stress-strain curve (i.e., higher Young’s modulus at 2% and 3% strain). Young’s modulus at peak strain also was significantly higher in EDL compared to MG/TA, whereas no significant difference was found between MG and TA. These results indicate that during natural loading, tendon Young’s moduli can vary considerably across muscles. This creates challenges to estimating muscle behavior in biomechanical models for which direct measures of tendon properties are not available.